Energy and exergy analysis of a modified air handling unit assisted by phase change material, heat recovery unit, and solar energy - Saman Faramarzi; Seyed Mohammad Mehdi Asadzadeh; Mohammad Reza Mohammad Hassani; Seyyed Amirreza Abdollahi; Reza Zarehzadeh; Mostafa Mafi (Scientific Reports)
Abstract This research focuses on designing an energy storage system using phase change material (PCM) in the air-conditioned zone, integrated with an air handling unit (AHU). The proposed system introduces a novel approach to reducing energy consumption in buildings by incorporating a solar heating coil and PCM. Through detailed energy and exergy analyses, the study evaluates the AHU’s performance and optimises the thickness and position of the PCM layer using genetic algorithm (GA) optimisation. Simulation of the proposed system was conducted using ASPEN Hysys and MATLAB software. Results demonstrate that integrating PCM reduces heat exchange by 687 kWh and optimising the PCM layer further improves system efficiency. Implementing a solar system decreases irreversibility by 7.3% compared to an AHU without solar integration, with a more significant reduction of 12.49% observed during hot months. Overall, the total irreversibility is reduced by 8%, with the solar system contributing to 80.6% of the irreversibility. These findings highlight the combined effect of PCM optimisation and solar integration in enhancing the energy and exergy performance of AHU systems.